A study on promotion strategies for ASN 3 at Permodalan Nasional Berhad Headquarters, Kuala Lumpur - Mohd Hamdan, Ahmad Adil (2003)
Promotion or marketing communication is a critical aspect of a company’s overall marketing mission and major determinants of its success. It is defined as the collection of all elements in a brand’s marketing mix that facilitate exchanges by establishing shared meaning with the brand’s customer or clients. The successful of a company’s sales objective results from a sound and good promotion strategies. Permodalan Nasional Berhad (PNB) was being set up on March 17, 1978, to act as investment arm. Since 1978 until 2002, PNB had launched many types of unit shares scheme under two types of price, variable price and fixed price and in this study, was only focus on the latest product of PNB which is called ASN 3. Amanah Saham Nasional 3 (ASN 3) which was launched on October 16, 2001 with approved fund size of 1 billion units. The ASN 3 Balance Fund unit trust is being launched more than a year. From approved fund size of one billion units, only 53 millions (5.3%) millions shares were sold within a year (as at 30 November 2002). It is considered as a small amount compared to other similar unit trusts of PNB such as ASM. Many factors might be contributed towards the low demand of ASN3, but the most important factor which possibly affects the demand of ASN 3. is lack of promotion or the promotion strategies which was being implemented by ASNB is less effective. Based on this problem statement, several objectives were being set up in order to settle this problem: (1) To measure the level of awareness for ASN 3 among public, (2) To study the effectiveness of promotion strategies made by ASNB towards the product of ASN 3, (3) To determine the strengths and weaknesses of promotional strategies made by ASNB for ASN 3 and (4) To recommend several improvement in promotion strategies for ASN 3 in order to increase quantity of investors. 70 sets questionnaires were distributed to the people at Klang Valley who made transaction at ASNB counter and they were selected randomly. The data were gathered and analysed by using SPSS program to get the frequencies distribution and cross tabulation results. Results for this study were divided into 5 sections: (1) Profile of the respondents, (2) The level of awareness for ASN 3, (3) The level of effectiveness for promotion strategies of ASN 3, (4) The strength and weaknesses of promotion strategies of ASN 3 AND (5) The improvement in promotion strategies for ASN 3. Based on the profile of the respondents, most of them are female with 51.4%, and majority of respondents were aged between 18 to 25 years old with 44.3%. As for marital status, majority of the respondents are married with the percentage of 51.4% and in terms of race, most of them were Malays with 74.3%. 40% of them are SPM holders, and 31.4% are working at executives’ level in terms of occupation, and majority of income were RM1001 to RM 3000 with 50%. Refer to the level of awareness for ASN 3, it also being found that most of the respondents with 68.6% know the existence of ASN 3, and 32.9% from the 70 respondents were the investor of ASN 3. 28% out of 70 respondents who didn’t know the existence of ASN 3 claimed that they didn’t have any information about it. In the measurement of effectiveness promotion strategies, 51.4% out of 70 of the respondents had been seen and heard the promotion for ASN 3, whereby most of them (22.9%) had seen or heard ASN 3 from advertising. It also showed that the most effective promotion tools that can influence them to invest in ASN 3 is advertising (52.9%). Furthermore, 41.4% of the respondents claimed that publicity can influence them to invest. While 34.3% of the respondents chose either salesperson campaign and talks and seminars as the effective promotion tools that can influence them to invest in ASN 3. In terms of determining the strength and weaknesses of promotion for ASN 3, several of promotion strategies had been found whereby ASN 3 promotion is still weak in providing enough information, attracting new investors and attract ASN 3’s investors to increase their investment. While the strengths of promotion for ASN 3 is in attracting people attention towards ASN 3 and influence investor to keep their investment in ASN 3. Therefore, ASNB needs to improve their promotion strategies, in terms of increasing advertising in electronic and printed media, enhance salespersons’ campaign, and finally give more talks and seminars in order to increase the number of investors for ASN 3.